2022
DOI: 10.4187/respcare.09987
|View full text |Cite
|
Sign up to set email alerts
|

High-Flow Nasal Cannula Versus Noninvasive Ventilation in Patients With COVID-19

Abstract: BACKGROUND: High-flow nasal cannula (HFNC) oxygen and noninvasive ventilation (NIV) have been widely used in patients with acute hypoxic respiratory failure (AHRF) due to COVID-19. However, the impact of HFNC versus NIV on clinical outcomes of COVID-19 is uncertain. Therefore, we performed this meta-analysis to evaluate the effect of HFNC versus NIV in COVID-19-related AHRF. METHODS: Several electronic databases were searched through February 10, 2022, for eligible studies comparing HFNC and NIV in COVID-19-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 53 publications
(154 reference statements)
0
9
0
Order By: Relevance
“…In our meta-analysis, we found that there were no differences in intubation rate, PaO 2 /FiO 2 , ICU LOS, hospital LOS, or VFD between the NIV and HFNC group, but mortality was significantly higher among COVID-19 patients in the NIV group, consistent with three recent meta-analyses. 36 38 Whether this was because of the delayed intubation and increased mortality in the NIV group is still unclear. In general, the role of NIV is indeed controversial.…”
Section: Discussionmentioning
confidence: 99%
“…In our meta-analysis, we found that there were no differences in intubation rate, PaO 2 /FiO 2 , ICU LOS, hospital LOS, or VFD between the NIV and HFNC group, but mortality was significantly higher among COVID-19 patients in the NIV group, consistent with three recent meta-analyses. 36 38 Whether this was because of the delayed intubation and increased mortality in the NIV group is still unclear. In general, the role of NIV is indeed controversial.…”
Section: Discussionmentioning
confidence: 99%
“…It has been stated that noninvasive positive pressure ventilation should be used as early as possible to dilate the pulmonary blood vessels of patients, thereby maintaining pulmonary functional residual capacity, reducing intrapulmonary shunts, improving pulmonary ventilation, decreasing respiratory failure symptoms, reducing inflammation caused by hypoxia, and accelerating recovery [18]. The reason may be that noninvasive positive pressure ventilation is a form of artificial ventilation assisted by a nasal mask that connects the ventilator to the patient, with the ventilator providing positive pressure support [19]. When this positive pressure is reduced or withdrawn, the whole chest and lungs rebound, and gas is exhaled, which allows ventilation equivalent to physiological breathing and negative pressure ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis comparing HFNC and NIV in patients with COVID-19 pneumonia showed no significant differences between the two groups in terms of intubation rate, mortality and length of hospital stay. 47 …”
Section: Discussionmentioning
confidence: 99%